Analisis Penerapan Metode RCM Dan MVSM Untuk Meningkatkan Keandalan Pada Sistem Maintenance (Studi Kasus PG. X) - Lukodono, Rio Prasetyo; Pratikto, Pratikto; Soenoko, Rudy (Rekayasa Mesin, 2013)
Maintenance system on milling season is using of preventive and corrective maintenance program. However, implementation of the program is still not guided with adequate SOP (Standart Operation Procedure) especially on a specific areas. Downtime occurring during year 2012 on the season were of 241.83 hours. This impacts to loss of potential profits, labor costs, and production capacity. To cope the problem, the study proposes application of Maintenance Value Stream Mapping (MVSM) supported by Reliability Centered Maintenance method (RCM). RCM consists of FMEA, reliability analysis, and RCM Worksheet. For the reliability analysis this study uses easyfit 5.5 profesional, whereas for the MVSM describes actual activity of the maintenance. Based on the application and analysis, it is known there exist 3 machines that are in critical condition and they show having the highest downtime, namely : Unigrator, cane Carrier I, and Cane Carrier II. The result of this research are SOP for actual activity of maintenance, time interval of maintenance, and tipe of maintenance for the machines.Key Word: MVSM, RCM, SOP Maintenance, 5S, FMEA, RCM Worksheet